Climate change and its impact on ecosystem services and biodiversity in arid and semi-arid zones - Karmaoui, Ahmed, 1982- (IGI Global, 2019)
"This book explores the effects of climate change and the human pressure on biodiversity and ecosystem services in dry lands. It also focuses on how climate change impacts the biodiversity and the associated ecosystem services and how it can be overcome at various strategic policy formulations in local, national and international levels"--